AB062. SOH26AB_0218. Enhancing early supported discharge for surgical patients via a virtual ward: Air Quality Index (AQI) approach - Haram, Abdelhamed; Javid, Muhammad; Cullinan, Carolyn; O’Gorman, Patricia; Fleming, Christina; Peirce, Colin (Mesentery and Peritoneum, 2026)
Virtual ward provides hospital-level care in the community, reducing inpatient length of stay while maintaining clinical safety. The Health Service Executive (HSE) Virtual Ward at University Hospital Limerick (UHL) currently supports medical, respiratory, cardiology, gynaecology, orthopaedic, and intravenous (IV) pathways. With increasing pressure on surgical bed capacity, this project aimed to evaluate the feasibility of extending virtual ward services to selected general surgical patients.